'Free men we stand under the flag of our land': a transitivity analysis of African anthems as discourses of resistance against colonialism. Issue 5 (3rd September 2022) - Mwinlaaru, Isaac N.; Nartey, Mark
ABSTRACT : Recent studies on colonial discourse have demonstrated that the speeches of freedom activists in colonial Africa served as sites of resistance. One key text type that has, however, been neglected in the critical literature on the discourse of emancipation is the national anthem of colonised states. To fill this gap, the present study examines the discursive enactment of resistance in the anthems of former British colonies in Africa, focusing on the transitivity framework in systemic functional linguistics. Semantic and structural parallelisms across the anthems are identified as evidence of a collective memory, a cultural trauma reconfigured and reconstituted to reclaim a positive identity and project a desirable postcolonial future. They also foreground the motif of freedom and legitimise the African as the owner of the reclaimed territory. These procedures articulate an anti-imperialist and anti-establishment stance that provides hope, strength and encouragement to an oppressed group. This paper extends the scholarship on the discursive enactment of resistance by focusing attention on a context underexplored in the literature. It also illustrates the (re)construction of relevant ideologies in national anthems to stimulate desirable, progressive attitudes among citizenry in African states. The paper is furthermore significant to decolonial research and highlights the role of language in political decolonisation processes.